Analisis Peran Self-Asssessment dalam Pengembangan Karir pada Tenaga Kesehatan di Puskesmas Meutulang - Pinalisa, Pinalisa (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the role of self-assessment in career development of healthcare workers at Meutulang Community Health Center. The research method used is a qualitative approach with a descriptive design, and data were collected through in-depth interviews with healthcare workers, including doctors, nurses, and midwives. The results show that self-assessment has been routinely practiced by healthcare workers in the form of self-evaluation of performance, compliance with standard operating procedures (SOP), and reflection on work experiences. Self-assessment plays an important role in increasing self-awareness, work motivation, and the ability to identify individual strengths and weaknesses. This contributes to improving competence and career development of healthcare workers. However, the implementation of self-assessment still faces several challenges, such as subjectivity in self-evaluation, time constraints, and lack of structured guidelines. Therefore, organizational support is needed in providing a more integrated self-assessment system to enhance the effectiveness of career development among healthcare workers.